Loss of Livelihood, Wages, and Employment During the COVID-19 Pandemic in Selected Districts of Chhattisgarh in India, and Its Impact on Food Insecurity and Hunger - Jeyakumar, Angeline; Dunna, Devishree; Aneesh, Mitravinda (Frontiers in Public Health, 2022)
The COVID-19 pandemic has exacerbated the existing food insecurity in developing nations. The cumulative effect of restricted mobility to curtail the spread of the infection, loss of livelihood and income, worst affected the economically weaker sections. Our work examined the availability, accessibility, and affordability of food during the first wave of the pandemic using the FAO, HFIAS questionnaire, in a random sample (N = 401) from Kanker and Narayanpur districts in Chattisgarh, an Empowered Action Group state, in India. Total food security scores were derived by summing the individual scores. Percentages above and below the median scores were used to assess food insecurity. Proportion Z test was used to compare settings and a generalized linear model was used to determine the association between dependent and independent variables. Of the 63% non-tribal population, a greater percent experienced income loss (13.4%) and worried about not having sufficient food (40%). A significantly higher proportion from the non-tribal regions reported food scarcity in the household (34%) and experienced hunger (15%). Non-tribal participants (77%) scored ≤ median (score 8) demonstrating high food insecurity. The odds of poor food access increased in the non-tribal settings (B: 0.024, 95% CI: 0.011–0.051, P < 0.001), income between Rs. 10,000–29,000/- per month (B: 0.385, 95% CI: 0.146–1.014, P < 0.05) and among those experiencing total or partial income loss (B: 0.505, 95% CI: 0.252–1.011, P < 0.05). Urban residence increased the odds of poor food availability (B: 15.933, 95% CI: 3.473–73.096, P < 0.001). Being male (B: 0.450, 95% CI: 0.208–0.972, P < 0.05), and not experiencing income loss (B: 0.367, 95% CI: 0.139–0.969, P < 0.05) decreased the odds of poor availability and affordability (B: 0.153, 95% CI: 0.067–0.349, P < 0.001). Non-tribal setting increased the odds of poor affordability (B: 11.512, 95% CI: 5.577–23.765, P < 0.001) and hunger (B: 19.532, 95% CI: 7.705–49.515, P < 0.001). Being male (B: 0.445, 95% CI: 0.277–0.715, P < 0.05) and higher age (B: 0.936, 95% CI: 0.936–0.906, P < 0.001) decreased the odds of food insecurity as per the total food security score. While India is likely to experience multiple waves, actions urgent and targeted toward the needs of the vulnerable sections be prioritized to endure and overcome the impact of the pandemic.